O poder e a luta pela propriedade da terra no vale do rio Iconha/Piúma: o caso Thomaz Dutton Junior (1870-1906) - Prado, Solange Faria (2018)
When arriving at the town of Piúma, south region of Espírito Santo, in the early years of the 1870s, Thomaz Dutton Junior, an englishman and later a naturalized brazilian, wanted to be part of the "good society" and to be entitled to all the prerogatives that the group would provide. In the territory of Piúma, he acquired a large part of the bankrupt estate of João Baptista Rodocanachi, a greek business person who exploited hardwoods and commercialized them for civil and naval construction. At the Monte Bello farm, after installing english settlers, Thomaz Dutton became involved in legalland disputes with local bosses with whom he had interdependent relations, especially with Alexandrino Pires Martins and José Gonçalves Costa Beiriz, who hidden , a complex by local political disputes, by prestige, by good reputation and power. Within these disputes was the ownership of the land, a symbol of power and control, which led to insolvency. This study investigates the trajectory of Thomaz Dutton, based on Norbert Elias's theory of Configuration associated with the theory of Symbolic Power of Pierre Bourdier. It aims to understand how the practices of power are materialized in social relations, identifying the learning extracted from interdependent relations as well as the values constructed from them. Part of analysis of documentary sources, such as provincial reports, applications, minutes, letters and newspaper articles - corpus documental, dominant in this research - seeking traces in the content of the speeches inserted to know the society, it becomes possible to bring to the surface the local history of the territory of the valley of Iconha / Piúma in the space of time between 1870 and 1906 and thus to expose its peculiarities and singularities, inserting it in the context of the national and local history of Espírito Santo. Thus, using the theoreticalmethodological foundation already presented, it highlights the peculiarities and past achievements of the society that were still outside the field of experience and needed to be known to be part of the History of the Espírito Santo.